TEMA LITERAL SEBAGAI GAGASAN AWAL PROSES PENATAAN KARYA TARI PADA MATA KULIAH KOMPOSISI TARI DI PROGRAM STUDI PENDIDIKAN SENDRATASIK UNIVERSITAS PGRI PALEMBANG - Rochayati, Rully (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Problems that are often encountered by students Programs Study Dance and music drama education is difficulties the theme will be lifted into the form or dance. The prosess of determining the theme of dance is indeed not easy especialy when it relates to the basic motion that will be done. The importance of this writing so that students as beginner dance stylists can learn the basic stages of the work prosess. The research method used is descriptive qualitative by conducting obsevations, interveiws, and documentation and literature studies to clarify the theoretical study used. The results of research from each student who has carried out stages in a structured manner then the result achieved is that every student is able to prosess well and maximally, students are able to write and explain all literal themes, literal motion, and detemine the initial idea well too. Besides that students can also do and explain to then interpret ideas and visualize in the form of dance works.